WHITE LAND BRICKS COCONUT FIBER AS ALTERNATIVE BUILDING MATERIALS IN KUPANG NTT - KRISTIANA BEBHE; RICHARDUS DATON (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2021)
Kupang Regency, NTT is an area that has the potential for white soil and abundant coconut husk waste. The white soil of Kupang has a textured physical character, contains sand and coral floss and a little clay and has adhesiveness when water is added. Meanwhile, coconut coir is a natural fiber which is coconut fruit waste. Natural fibers such as coconut coir, apart from being able to lighten the weight of the bricks, are also expected to strengthen the bricks. In certain compositions, coco fiber can be used as an added material in brick making because it reduces cracking. (Mulyono 2004). The research method used is experimental research methods. The results of the measurement of the compressive strength of bricks added with coconut coir fiber, with a ratio of 1 coconut fiber: 1 cement: 7 white soil reached 147 kg / cm², this is much higher than previous studies using 1 cement: 7 white soil reaching 51.9 kg. / cm² and smaller than white earth bricks mixed with rice husks which reaches 83.7 kg / cm² (Bebhe, 2020). In addition, in the compressive strength test, the bricks with a mixture of coconut fiber after the test did not experience total destruction but only cracked on the edges of the brick.